Transformation Management Human Resources in the Defense Economy of the Global Era: Approaches Integrative between Policy, Industry and International Cooperation - Sri Sundari; Mia Kusmiati; Suca Rusdian; Nita Eldiani (International Forum of Researchers and Lecturers, 2025)
This study explores how human resource (HR) management functions as a strategic pillar in developing a resilient and adaptive defense economy in the global era. The research integrates national policies, defense industry power competition, and international collaboration through an HR-based global competence approach. The study employs a systematic literature review (SLR) method, analyzing over 50 peer-reviewed articles published in Scopus/WoS indexed journals between 2021 and 2025. The research synthesizes a framework that combines strategic human resource management, defense economics, and global collaboration. The findings reveal that HR is not merely an administrative function but plays a strategic role in strengthening defense through the development of human power, digital literacy, and international collaboration. The study further highlights that the success of defense industry synergies is largely influenced by the readiness of human resource actors to integrate innovation, diplomacy, and transnational knowledge. For practical implications, the study suggests that national defense policies must invest in specialized human resource development centers, design curricula aligned with global threats and technologies, and build strategic partnerships with international defense actors. This study is the first to conceptualize an integrative framework that places HR at the core of defense economy transformation in the post-pandemic, digitally driven global landscape, offering both theoretical novelty and practical relevance for policymakers and defense educators.